2022
DOI: 10.48162/rev.39.060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genotype-environment interaction on soybean (Glycine max L.) genetic divergence under semiarid conditions

Abstract: The objective of the present work was to evaluate the influence of the genotype–environment interaction on genetically divergent soybean grown under semiarid conditions. Four experiments were carried out in randomized blocks with four replicates to evaluate twenty-one soybean genotypes. The following descriptors were used to quantify divergence: plant height, dry matter, oil content, number of pods per plant, number of grains per pod, the weight of 100 seeds, yield, days for flowering, and days for maturation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For NG, Ghiday et al 30 reported a heritability of 0.98. Similarly, Del Conte et al 31 and de Albuquerque et al 32 reported heritability estimates of 0.70 and 0.59, respectively. For HGW, Bisinotto et al 33 , reported a heritability estimate of 0.77 using 31 lines from a breeding program.…”
Section: Genetic Parametersmentioning
confidence: 89%
“…For NG, Ghiday et al 30 reported a heritability of 0.98. Similarly, Del Conte et al 31 and de Albuquerque et al 32 reported heritability estimates of 0.70 and 0.59, respectively. For HGW, Bisinotto et al 33 , reported a heritability estimate of 0.77 using 31 lines from a breeding program.…”
Section: Genetic Parametersmentioning
confidence: 89%
“…It should also be noted that many of these variables were previously evaluated in other studies with coefficients of variation between similar ranges (26,41). Thus, our experimental precision may be considered adequate (5,45).…”
Section: Discussionmentioning
confidence: 99%